Medical wearable devices for tracking symptoms of COVID-19 - Rogers, John (Henry Stewart Talks, 2020)
What are medical wearables devices, COVID-19 specific medical wearable devices, Monitoring key parameters of physiological and pathological states, Advantages of wearable over current test & trace methods, Personalisation of public health responses using wearable devices, Companies currently involved in the development of COVID-19 wearables, Wider population access to COVID-19 monitoring wearables